PENGARUH POLITICAL CONNECTIONS TERHADAP KINERJA PERUSAHAAN - Agustinus Tri Kristanto (EXERO : Journal of Research in Business and Economics, 2019)
This study aimed to determine the effect of political connections on firm performance, especially a non financial institutions. The sample in this study is a non-listed financial institutions in Indonesia Stock Exchange in 2010-2012, amounting to 304 companies. The dependent variable in this study is the ROE and Tobins'q. While the independent variable in this study is the proportion of independent directors who are politically connected and the proportion of managerial ownership has political relations, company size and type of company. The hypothesis was tested by multiple linear regression. From the tests, it was found the proportion of independent directors who have political ties have a negative effect on the financial performance of the company, while the proportion of managerial ownership has political ties have a negative effect on market performance.